Multibeam bathymetry processed data (Kongsberg EM 122 entire dataset) of RV SONNE during cruise SO246, Chatham Rise, South Pacific Ocean - Karsten Gohl; Simon Dreutter; Florentina Münzer; Rosa Crespo; Boris Dorschel (PANGAEA, 2024)
Multibeam data were collected during RV Sonne cruise SO246 (2016-02-01 to 2016-03-21). Multibeam sonar system was Kongsberg EM 122 multibeam echosounder. Data are processed with Caris HIPS, including sound velocity correction with SV data from CTDs and World Ocean Atlas 18 (https://www.ncei.noaa.gov/archive/accession/NCEI-WOA18), tidal correction with TPXO9_atlas_v5 (https://www.tpxo.net/global/tpxo9-atlas), and manual cleaning. The soundings are combined in daily files, the format is XYZ ASCII (<Lon> <Lat> <Depth in meters, positive up, relative to mean sea level>). Additional grids have been computed with depth dependent cell size to visualize the data. These grids are not meant for scientific analysis or navigation, but for overview purposes only.